2006
DOI: 10.1007/s00535-006-1848-4
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor induces rectal hypersensitivity after repetitive painful rectal distention in healthy humans

Abstract: These results indicate that CRF modifies rectal sensation in healthy humans and mimics an IBS-specific visceral response, suggesting the possible contribution of CRF to the pathogenesis of IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…In light of the recent increasing interest in the potential modulating effects of CRF in clinically relevant pain conditions such as visceral pain (Nozu and Kudaira, 2006;Sagami et al, 2004), postoperative joint pain (Likar et al, 2007), and fibromyalgia (McLean et al, 2006;Lund et al, 2006), we set out to investigate systematically the antinociceptive effects of CRF at the three main levels of the neuraxis of pain transmission, that is, at the level of the brain, spinal cord, and periphery. As it was suggested that antinociceptive effects of CRF are identified rather in tonic than in phasic pain (Lariviere and Melzack, 2000), we have chosen an animal model of tonic pain, that is, Freunds complete adjuvant (FCA) hindpaw inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the recent increasing interest in the potential modulating effects of CRF in clinically relevant pain conditions such as visceral pain (Nozu and Kudaira, 2006;Sagami et al, 2004), postoperative joint pain (Likar et al, 2007), and fibromyalgia (McLean et al, 2006;Lund et al, 2006), we set out to investigate systematically the antinociceptive effects of CRF at the three main levels of the neuraxis of pain transmission, that is, at the level of the brain, spinal cord, and periphery. As it was suggested that antinociceptive effects of CRF are identified rather in tonic than in phasic pain (Lariviere and Melzack, 2000), we have chosen an animal model of tonic pain, that is, Freunds complete adjuvant (FCA) hindpaw inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated a greater increase in perception of colonic distension after intravenous CRH administration in healthy individuals, in contrast to the response prior to administration or following placebo. 18 Another study reported that when a-helical CRH was peripherally administered in IBS patients, the hyperresponsiveness to stress induced by colonic electrical stimulation was suppressed. 8 These results indicate that stress is closely associated with colonic perception and bowel movements.…”
Section: Discussionmentioning
confidence: 99%
“…An alteration in central noradrenergic signaling is observed in IBS; early life trauma may be one mediator of these abnormalities [ 20 ]. In healthy controls, CRF iv decreases rectal pain threshold to distension and mimics an IBS-specifi c visceral response [ 137 ]. Peripheral injection of α-helical CRF9 − 41 prevents rectal electrical stimulation-induced enhanced sigmoid colonic motility, visceral perception, and anxiety in IBS patients compared to controls without altering the HPA axis [ 161 ] and improves decreased alpha power spectra and increases beta power spectra of electroencephalogram in IBS patients [ 190 ].…”
Section: Implication In Functional Digestive Disorders and Infl Ammatmentioning
confidence: 98%